PERBANDINGAN HASIL BELAJAR SISWA DENGAN MODEL PICTURE AND PICTURE DI SDN PUCANG 4 SIDOARJO - Endang eryanti; Risdiana Chandra Dhewy (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2022)
This study uses the Picture and Picture model for grade 3A students on the flat shape material. The purpose of the study was to determine whether or not there were differences in student learning outcomes before and after using the Picture and Picture model, but it also aimed to determine student responses to learning. The sample used was 32 students. The test method and the provision of response questionnaires are methods for collecting data for this activity. There are 10 test questions for the pretest and posttest. The response questionnaire consists of 7 indicators. After analyzing the data, it shows the conclusion that the data is not normally distributed so that the data transformation is carried out and the results show that the data is still not normally distributed. Therefore, the researchers chose nonparametric statistical techniques as the solution by using the Wilcoxon test. The test results show that there are differences in student learning outcomes before and after the Picture and Picture model with an average value of 90.34 pretest and 91.50 posttest.